Larvicidal activity of raw sentang leaves against aedes aegypti (linnea us) - Ba'in, Arba'iyah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2006)
Sentang (Azadirachta excelsa) that have been reported to possess larvicidal properties mainly due to the nature of the specific chemical constituents found in the plant namely azadirachtin. The purpose of the study was to evaluate the toxicity of raw sentang leaves as larvicide against Aedes aegypti mosquitoes under laboratory conditions. Sentang leaves were grinded and stirred in water to make treatment of different ranging from 400 to 2000 ppm. Bioassays on the toxicity of the solutions were conducted out against the third instar larvae of Aedes aegypti for a period 21 days. The result of the first 6 days showed that the solution of higher concentration ( 1600 and 2000 ppm) caused high mortality compare to the lower concentration and control. At day 6, the percentage of cumulative mortality for the 1600 ppm is 28.0% and 2000 ppm is 42.4%. However, at day 12 onwards larvae of Aedes aegypti mosquitoe seems can survive in the treatment when compared to the control that shows highest mortality (93.6% cumulative mortality at day 21). It is suggested that sentang's leaves also provide some nutrient to the larvae for its survival and at the same time inhibit the growth and development of larvae. The results obtained from this study indicated a promising role of sentang as botanical larvicide against Aedes aegypti mosquitoes.